Uterine damage induces placenta accreta and immune imbalance at the maternal-fetal interface in the mouse. (4th March 2022) - Zhou, Jiayi; Chen, Huanpeng; Xu, Xiuting; Liu, Yunyun; Chen, Shengzhu; Yang, Si; He, Fang; Yu, Bolan
Abstract: Introduction: Placenta accreta spectrum (PAS) disorder is one of the major complications resulting in maternal death and serious adverse pregnancy outcomes. Uterine damage — principally that associated with cesarean section — is the leading risk factor for the development of PAS. However, the underlying pathogenesis of PAS related to uterine damage remains unclear. Methods: For this study, we constructed a mouse PAS model using hysterotomy to simulate a cesarean section in humans. Pregnant mice were sacrificed on embryonic days 12.5 (E12.5) and E17.5. Trophoblast invasion and placental vascularization were analyzed using Hematoxylin-Eosin (H&E) staining and immunohistochemistry (IHC), and the proportions of immune cells at the maternal-fetal interface were analyzed using flow cytometry. We analyzed the expressions of genes in the decidua and placenta using RNA sequencing and subsequent validation by QPCR, and measured serum angiogenic factors by ELISA. Results: Uterine damage led to increased trophoblast invasion and placental vascularization, with extensive changes to the immune-cell profiles at the maternal-fetal interface. The proportions of T and NK cells in the deciduas diminished significantly, with the decidual NK cells and M − 2 macrophages showing the greatest decline. The expression of TNF-α and IL4 was upregulated in the deciduas, while that of IFN-γ and IL10 was downregulated significantly. The expression of Mmp2, Mmp9, Mmp3, and Dock4 was significantly elevated in the placenta, and the serum levels of anti-angiogenic factors were significantly attenuated. Discussion: Uterine damage can cause immune imbalance at the maternal-fetal interface, which may contribute to abnormal trophoblast invasion and enhanced vascularization of the mouse placenta. Highlights: Uterine damage led to increased trophoblast invasion. Uterine damage led to altered immune cell profiles at the maternal-fetal interface. Levels of inflammatory cytokines changed in the deciduas. Cell invasion and angiogenesis related genes were up-regulated in the placenta.